Intermediation networks and derivative market liquidity: evidence from credit default swap markets - Mark, Paddrik; Stathis, Tompaidis (Review of Finance, 2026)
Abstract In over-the-counter markets, dealers facilitate trade by providing liquidity and acting as intermediaries. We use proprietary data on US single-name credit default swap trades and positions to study how dealer intermediation networks shape liquidity. For each reference entity, we reconstruct interdealer and dealer-to-client networks and introduce Shapley value-based measures of dealer and market connectivity. We present a cooperative game framework that links these measures to predictions for the liquidity that dealers provide at both individual and market levels. Empirically, we find that Shapley values are strongly associated with trade volumes, inventory management, execution costs, and bid–ask spreads.